Increase of cd4+cd25highfoxp3+ cells impairs in vitro human microbicidal activity against mycobacterium tuberculosis during latent and acute pulmonary tuberculosis - Stringari, Lorenzzo Lyrio (2021)
50204076]. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript. Publisher Copyright: © 2021 Stringari et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.